Slovak Republic : 2009 Article IV Consultation; Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2009)
This 2009 Article IV Consultation highlights that following a period of rapid growth, economic activity in the Slovak Republic tumbled in the first half of 2009 as a result of the global crisis. Slovakia's banks have so far withstood the global crisis relatively well. Executive Directors have encouraged the authorities to formulate and announce a credible medium-term fiscal consolidation strategy, aimed at bringing down the general government deficit to within the Maastricht norm in a timely manner. Directors have also emphasized that external competitiveness will require sustained structural reforms and wage discipline.